Commensal Bacteria-Dependent CD8αβ+ T Cells in the Intestinal Epithelium Produce Antimicrobial Peptides - Chen, Banru; Ni, Xiang; Sun, Rui; Zeng, Benhua; Wei, Hong; Tian, Zhigang; Wei, Haiming (Frontiers in Immunology, 2018)
The epithelium of the intestine functions as the primary “frontline” physical barrier for protection from enteric microbiota. Intraepithelial lymphocytes (IELs) distributed along the intestinal epithelium are predominantly CD8+ T cells, among which CD8αβ+ IELs are a large population. In this investigation, the proportion and absolute number of CD8αβ+ IELs decreased significantly in antibiotic-treated and germ-free mice. Moreover, the number of CD8αβ+ IELs was correlated closely with the load of commensal microbes, and induced by specific members of commensal bacteria. Microarray analysis revealed that CD8αβ+ IELs expressed a series of genes encoding potent antimicrobial peptides (AMPs), whereas CD8αβ+ splenocytes did not. The antimicrobial activity of CD8αβ+ IELs was confirmed by an antimicrobial-activity assay. In conclusion, microbicidal CD8αβ+ IELs are regulated by commensal bacteria which, in turn, secrete AMPs that have a vital role in maintaining the homeostasis of the small intestine.